Pengaruh Suplementasi Protein terhadap Komposisi Tubuh pada Atlet - Setiowati, Anies; -, Hadi (Universitas Negeri Semarang, 2013)
This study aimed to determine the effect of protein supplementation on body composition (body weight, percent body fat and muscle mass). The method used experimental study group pre-post test design. Samples were students in football athletes SMA Terang Bangsa Semarang aged 15-18 years as many as 11 people. Treatment of samples for the provision of as much as 30 grams of protein supplements for 4 weeks. Weighing is done with a digital scale, percent body fat was measured by bioelectrical impedance analyzer (BIA) Corona brand. Data were analyzed using the Paired t-test / Wilcoxon. The results of the statistical test Paired t-test / Wilcoxon there are differences in the results obtained decrease percent body fat (pre 19,1±1,1%, post 17,9±1,2%, p = 0.003) and an increase in lean body mass (pre 51,4±5,5 kg, post 52,4±5,5 kg, p = 0.013) after administration of a protein supplement. No difference in change in body weight after treatment. Conclusion: protein supplementation for 4 weeks can lower percent body fat and increase lean bodymass.